Dampak Pergaulan Bebas terhadap Implementasi Pemahaman Agama - Laudza Zulfa Nur Dipa (Jurnal Dirosah Islamiyah, 2022)
Association is a group or individual interaction because human nature is social beings who need each other. The social form in society will be formed by the association between other people, ethnicity, race and religion. The formation of associations will be influenced by two factors, namely healthy factors and unhealthy factors. The policy of a human being in the adolescent environment must be able to choose the good, sometimes among students still have a wavering or unstable nature in choosing a good or bad problem. However, change will always develop in humans or students. The change is an understanding in understanding religious issues. Understanding religion makes a guide and wasilah in carrying out the life of the world. This will make the basis of association according to religion. So with that research is interested in investigating the title of the impact of promiscuity on the implementation of religious understanding at SMK 1 & 2 Ciawi, with the aim of wanting to know the extent to which students understand religion in their daily lives, and wanting to know the impact of promiscuity in the school. This research uses a qualitative descriptive method through a case study approach. Data collection techniques through observation, documentation and interviews. This research method uses the triangulation method with an approach to teachers, students, and parents. So the results of this study have the impact of promiscuity in the implementation of religious understanding in schools, including: the existence of a relationship with the opposite sex, slowing down the prayer service, saying ah to parents, speaking rudely, and not wearing a headscarf in their home environment. Keywords: Religion, Understanding, Association